Female Guinea Pig Model for Cough Studies and Its Response to Most Common Tussive Substances - Sterusky, M; Plevkova, J; Grendar, M; Buday, T (Physiological research, 2020)
Laboratory research of cough reflex utilizes almost exclusively male guinea pigs - a practice that represents a significant obstacle in the successful translation of results into clinical practice. Chronic hypersensitivity cough syndrome affects mostly postmenopausal women and it represents significant decrease in patient's quality of life. No cause for such exaggerated cough can be found, therefore this condition cannot be treated appropriately. One of the reasons leading to the lack of relevant data about mechanisms responsible for hypersensitivity of cough related pathways is nowadays widely discussed gender bias, which is present in nearly all branches of biomedical research. Since gender differences in cough reflex physiology do exist in humans, it would be reasonable to study cough-related phenomena on both sexes of laboratory animals. In this study, we focused on detailed characterization of cough response of female guinea pigs to aerosols of commonly used tussive agents (capsaicin, distilled water, allyl isothiocyanate, cinnamaldehyde, citric acid). In pooled data from multiple challenges we found no statistical difference in number of cough and cough latency between sexes. Based on our results we conclude that the utilization of female guinea pigs model does not lead to messy data and can be used in basic cough research.
Keywords: Female; kyselina citronová; akrolein; Capsaicin; zvířata; Guinea Pigs; ženské pohlaví; Male; Citric Acid; Sex Characteristics; Cough; morčata; pohlavní dimorfismus; kapsaicin; kašel; Animals; Acrolein; mužské pohlaví; Disease Models, Animal; modely nemocí na zvířatech